Does Money Triumph over Identity? a Survey Findings from the Local Levels - Saputra, Andhik Beni; Setiawan, Azhari (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
In this article, we try to analyze which factors emerged as the strongest determinants of voters’ behavior in a new democratic country dominated by the web of patronage and clientelistic exchanges. We examine two main variables in this study, vote buying and identity politics. Previous studies on electoral clientelism in Indonesia are mostly centered on its causes and mechanisms as an electoral strategy to garner electoral votes during an election. The socio-political contexts that follow the electoral dynamics are less explained. Initially, we assume that the intensive mobilization of identity politics that made the 2019 Indonesia election more explosive would decrease since voters would also solidify their voting preference into identity lines. However, through a post-election survey at the local level by selecting four districts (N=503), we find that vote buying emerges as a more robust variable in driving voters’ behavior rather than identity politics. Moreover, regional differentiation – land and coastal areas – also matter in this study where voters in the coastal regions are more likely to accept material inducements from candidates. Finally, our findings add many tasks for Indonesian democracy since clientelistic exchanges work as a more effective instrument for affecting voters' decision-making in elections rather than programmatic politics.